Use of ultra-freezers of -152 °c as a viable alternative to liquid nitrogen in storing - Israa Mahmoud Alhamad; Mehmet Borga Tirpan (Eurasian Journal of Veterinary Sciences)
Aim: This study aims to investigate the utilization of the ultra-freezer to store the semen at a -152 °C as an alternative method to traditional semen storage methods. Materials and Methods: A total of 80 straws were collected from two bulls on different days. The semen collected on the same day were sorted into two different groups. The experimental group of the study was composed of sperm stored at -152 °C for one week, while the control group was composed of sperm stored at -196 °C using the traditional storage method. At the end of the experimental period, frozen semen at -196 °C and -152 °C were thawed at a temperature of 37 °C water bath for 30 seconds. Then, the spermatological parameters and morphological properties of the sperm were examined by using a computer-assisted sperm analysis system (CASA). Results: The evaluation of semen samples yielded the following results; the motility and progressive motility of the frozen and stored sperm (69.66%; 37.61%) at -196 °C were higher than the values (54.54%; 28.72%) stored at -152 °C (p<0.001). The percentage of sperm with hyperactivity in group -196 and -152, was found to be 30.79% and 25.61%, respectively, (p<0.05). There was no statistical difference between kinetic values, and it was close to numerical values (p>0.05). Moreover, it was determined that the abnormal sperm rate was at 32% for the semen stored in liquid nitrogen and was 45% for the semen stored at -152 °C (p <0.001). Conclusion: As a result of the experiment, it was determined that the postthawing parameters of the sperms stored in -152 °C freezer were within acceptable ranges.